The Potential of Soy Isoflavones (Glycine max) and Magnetic Hydroxyapatite Nanoparticles as Osteoporosis Therapy for Menopausal Women - Ayik Rochyatul Jannah; Faiza Rahma Ebnudesita; Savira Butsainah Dienanta; Reny I’tishom (Indonesian Andrology and Biomedical Journal, 2020)
Background: Menopausal women experience amenorrhea for 12 consecutive months. In Indonesia, one of four women aged 50 – 80 years has a risk of osteoporosis. This age range is related to the menopause phase. Low estrogen levels in menopausal women cause decreased bone mineral density resulting in osteoporosis. Osteoporosis is a degenerative disease characterized by decreased bone density and bone strength that causes fractures. This literature review aims to determine the potential of soy isoflavones (Glycine max) and magnetic hydroxyapatite nanoparticles as alternative therapies for osteoporosis in menopausal women.Reviews: Soy isoflavones are phytoestrogens because they have estrogen-like structures and functions. Some studies explain that phytoestrogens have benefits in osteoporosis therapy by maintaining bone density through decreasing osteoclast resorption and stimulating osteoblasts. Consuming enough soy supplements everyday has been shown to increase bone mineral density. This effect is strengthened by coating the soy isoflavones with magnetic hydroxyapatite nanoparticles through two mechanisms, as a therapeutic agent and drug carrier. The magnetic field of the magnetic nanoparticles produces force and torque to increase the temperature until 42°C  and trigger organelles movement, causing apoptosis of osteoclasts. Hydroxyapatite is a major component of bone mineral that replaces bone tissue deformity and has an osteoblastic effect in bone regeneration. Nano-sized hydroxyapatite will increase material properties and stability in high temperatures. However, hydroxyapatite has less magnetic activity so this function is completed by magnetic nanoparticles.Summary: Therefore, the combination of soy isoflavones and magnetic hydroxyapatite nanoparticles works synergistically as an alternative therapy for osteoporosis in menopausal women.